Mapping the Parenting Style: A Child-Perspective Study at Darul Hikmah Islamic Full-Day Elementary School - Atikoh, Nur; Kim Thi My Nguyen (UIN Sunan Kalijaga Yogyakarta, 2025)
This study aims to identify the predominant parenting styles among Grade VI students at MI Darul Hikmah Full Day School in Cirebon City, Indonesia. Employing a quantitative descriptive approach, the research utilized a structured questionnaire as the primary data collection instrument, distributed to 34 Grade VI students enrolled at the institution. The findings revealed that most respondents (59%) perceived their parental upbringing to align with the